Translating Problems of English Complex Sentences Connected with “Least” into Uzbek - Zokirova Dildora Muydinovna (Genius Journals, 2022)
This article discusses translating problems of English complex sentences connected with “least” into Uzbek. It studies different methods and ways of translating sentences and the usage of “least” in different complex sentences in compared languages.
Keywords: complex; connection; “least”; semantic